Public policymaking in a globalized world - Lewis, Robin J. (London Routledge, 2018)
"The inexorable advent of globalization has transformed the public policymaking process into a multi-faceted challenge that transcends traditional policymaking boundaries and forces scholars, experts, and practitioners to redefine their field in terms of both theory and practice. While every policy dilemma has a specific location in time and space, most significant policy issues-- climate change, food and water, economic development, global pandemics, terrorism and violence, and migration, to name just a few--now require a collective framing of the problem and a collaborative effort to take effective action."--Publisher's description
Part I. Governance and the policy process -- Part II. Reflections on policymaking and policy analysis -- Part III. Global case studies: India, China, Egypt, South Africa and Rwanda -- Part IV. Public policy in Turkey: sectoral perspectives
Includes bibliographical references
Keywords: Political planning -- Case studies; Political planning -- International cooperation; Administrative agencies; Conflict management; Policy sciences